2021
DOI: 10.1039/d0bm01801e
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human cord blood plasma accelerate cutaneous wound healing by promoting fibroblast function, angiogenesis, and M2 macrophage differentiation

Abstract: Exosomes contain natural cargo molecules, such as miRNA, mRNA, and proteins, and transfer these functional cargos to neighboring or distant cells through circulation. In the wound-healing process, exosomes in human...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…showed that human cord blood plasma EVs also promoted wound healing. Especially in EVs, heat shock protein 72 (HSP72) and prolactin-inducible proteins (PIPs) also promote differentiation from the proinflammatory M1-like phenotype to the anti-inflammatory M2-like phenotype, thus promoting the transition of wounds from inflammation to proliferation ( 110 ). Adjusting the EV/macrophage axis to reduce skin inflammation may become a new treatment approach for diabetes complicated with skin healing disorders in the future.…”
Section: Ev/macrophage Axis and Inflammatory Diseasesmentioning
confidence: 99%
“…showed that human cord blood plasma EVs also promoted wound healing. Especially in EVs, heat shock protein 72 (HSP72) and prolactin-inducible proteins (PIPs) also promote differentiation from the proinflammatory M1-like phenotype to the anti-inflammatory M2-like phenotype, thus promoting the transition of wounds from inflammation to proliferation ( 110 ). Adjusting the EV/macrophage axis to reduce skin inflammation may become a new treatment approach for diabetes complicated with skin healing disorders in the future.…”
Section: Ev/macrophage Axis and Inflammatory Diseasesmentioning
confidence: 99%
“…RBCEVs are critical for the dysregulation of hemostasis and exhibit associated procoagulant effects in several diseased states [ 54 ]. Exosomes from human cord blood plasma play an important role in wound healing by promoting angiogenesis and the differentiation of M2 macrophages, thereby facilitating the transition from inflammation to proliferation [ 57 ].…”
Section: Roles Of Rbcevs In Healthy and Diseased Statesmentioning
confidence: 99%
“…In recent years, EVs have been widely used as natural delivery vehicles for intercellular nucleic acids, [ 3 ] proteins, [ 4 ] as well as drugs [ 5 ] aimed at modulating immune responses, [ 6 ] cell proliferation, [ 7 ] and angiogenesis. [ 8 ] EVs also have great clinical application potential against tumor cells, [ 9 ] promote bone regeneration, [ 10 ] and wound healing, [ 11 ] which are essential for the treatment of diseases such as diabetes, [ 12 ] spinal cord injury, [ 13 ] and heart injury. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%